(untitled) (Indian Journal of Arid Horticulture, 2025)
Pruning is very effective to induce healthy current season growth. ft also responds to slow growing trees by maintaining the size and shape without sacrificing yield. Further, proper nutrient management is als-0 essential to maintain soil fertility and plant nutrient supply to an optimum level. The aonla plant responses the light as well as severe pruning. Thus, an investigation on response of pruning and nutrient management on vegeiative growlh and fruit yield has been conducted during the two consecutive years. The maximum increase in vegetative growth characteristics, fruit yield and quality was found in 50% pruning intensity along with nutrient management by use ofFYM (40 kg) and NPK ( I 000:500: l000 g/plant). Since, pruning remove carbon-starved, fruiting exhausted shoots and promotes new leaf growth to build up carbohydrate reserves for the next flowering tha( allows the sprouting of lateral buds hence, ultimately influenced the plant gro 1h, spread, trunk girth and other vegetative characteristics of the plants. The significant interactive effect of treatments was attributed to the favourable nutritional status of the leaf and soil resulting into increased biomass production of the fruit. A significant increase in yield and yield parameters in aonla with nutrient application would have been due to vigorous vegetative growth and increased chlorophyll content, which together accelerated the photosynthesis that increased the supply of carbohydrates to plants.